EVALUASI PENERAPAN SISTEM HARMONISASI GLOBAL DI PT PETROKIMIA GRESIK PABRIK 1 UNIT UREA - M.Isa Rosyidi Asror; Erwin Dyah Nawawiwetu (Universitas Airlangga, 2018)
The presence of Globally Harmonized System (GHS) in the world can not be separated from the element of risk and danger of the chemicals which are used both for humans and for the environment. PT. Petrokimia Gresik is one of companies which use a wide various of hazardous chemical elements. In the process of production and the products themselves, as found in Production Process Urea Unit. PT Petrokimia Gresik start to implement GHS in 2009 based on the regulations of the Minister of Industry No. 87/M-IND/PER/9/2009 about Globally Harmonized System of Classification and Labels On Chemicals. This study aimed to Evaluate of the implementation of the GHS as an illustration of condition of GHS application on PT. Petrokimia Gresik factory 1 unit urea. This research is descriptive study. Subjects in this study is a variety of work related to the implementation of the GHS in the urea unit and the object of this research is the implementation of the GHS. This study variables include the application of GHS such as dangers, and SDS / LDK. The results of the study showed that the GHS of PT Petrokimia Gresik had been adequately implemented (66%), because it only fulfills 2 variables from 3 variables tested. Keywords: evaluate, globally harmonized system, illustration